The legal regulation of children recruitment and participation in armed conflict under international humanitarian law - Gurajena, Thomas (2017)
This dissertation explores the legal regulation of children recruitment and participation in armed conflict under international humanitarian law (IHL), addressing how IHL protects children aged between 15 and 18 years. It assesses whether IHL has done so in a manner which proffers adequate legal protection such that there is no need for other branches found international law to chip in to close gaps or weaknesses. This dissertation interrogates the IHL regime as well as other discourses in international law. It highlights that IHL instruments protect children aged below 15 years from recruitment and participation in armed conflict but fails to cover all situations which expose children from the perils of war. This study proves that whereas customary international law and IHL has laid the minimum age of recruitment and participation in armed conflict, now used in international criminal law, state practice shows that states are evolving towards a ‘straight 18 position’. For this reason states whose domestic laws permit recruitment of children below 18 years face criticism for their recruitment policies. In addition, the research acknowledges the stance adopted by African states in the African Children’s Charter. It recommends that other regional blocks should adopt guiding principles or declarations which raise the minimum age of recruitment from 15 – 18 years as the whole international community gears towards embarking on establishing an international convention reflecting a ‘straight 18 position’.